Association between hemoglobin and non-alcoholic fatty liver disease (NAFLD) in United States adults: Results from NHANES 2017–2020 - Kang Yao; Zheng Chen; Wei Zhou; Zhihua Liu; Wei Cui (Preventive Medicine Reports, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD), a chronic liver condition of increasing prevalence, is closely related to various metabolic disorders. Hemoglobin, a protein that transports oxygen in red blood cells, is the focus of this study, which seeks to investigate its potential association with NAFLD. Methods: We selected 6,516 eligible adult participants from the United States using the 2017–2020 National Health and Nutrition Examination Survey database for cross-sectional analyses. We analyzed the association of hemoglobin with NAFLD using weighted logistic regression models. Results: The study performed a weighted logistic regression modeling analysis, which verified that hemoglobin levels were positively associated with NAFLD, especially in the higher hemoglobin quartile groups. Subgroup analyses revealed no significant interactions, demonstrating the robustness of the model. The analysis of mediation effects showed that Gamma-Glutamyl Transferase, Alanine Aminotransferase, and triglycerides were important mediating variables in the relationship between hemoglobin and NAFLD. Conclusion: Increased hemoglobin levels were found to be significantly and independently associated with an increased NAFLD risk. This insight is crucial for the risk assessment and early detection of NAFLD, underscoring the need for heightened vigilance in individuals with higher hemoglobin levels.